Exploring the Celestial Transformation: Calling and Provision a Heuristic Study - Khumalo, Mandla (UIN Sjech M. Djamil Djambek Bukittinggi, 2024)
The aim of this paper is to explore the concept of God’s divine calling and His provision for Ministers within the Christian faith using heuristic inquiry framework. It argues that God calls Ministers of the Gospel of Jesus Christ to service and provides accordingly for the sustenance of that call. Firstly He calls them into knowing and obeying Him. That ultimately, leads to service. What does spiritual calling entails? What are the perceptions of God’s call to his disciples? How does God call disciples into Ministry? These are the three questions the study attempted to contribute answers to. Data was collected from seven co-researchers who were between 29 and 54 years of age. Semi-structured interviews were used to collect the data. The data was analyzed and synthesized using Moustakas (1990) approach and four themes emerged. The results revealed that there are different approaches used by God to call His people into Ministry. The age and gender are not the major variables considered in the calling. The study concluded that a relationship with God is an important factor in the call of the Lord.